Interactive Edugame-Based Learning Media to Improve Science Learning Outcomes of Sixth-Grade Elementary School Students - Ni Kadek Eliyanti; I Wayan Suastra; Ni Ketut Suarni (Jurnal Media dan Teknologi Pendidikan, 2025)
The lack of innovation in the use of engaging, interactive, and enjoyable learning media has contributed to low student motivation and learning outcomes in science instruction. This study aims to analyze, examine, and evaluate the validity, practicality, and effectiveness of an Edugame based interactive learning medium in enhancing students’ motivation and learning outcomes. This research employed a development research design using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research subjects involved teachers and 31 students. Data were collected through expert validation questionnaires, teacher practicality questionnaires, and pretest and posttest instruments to measure learning improvement. Data analysis utilized the Gregory formula to determine the level of media validity and N-Gain analysis to measure the increase in students’ conceptual understanding. The results indicated that the Edugame-based media achieved a very high level of validity (90%) and a very high level of practicality (96%). Furthermore, the effectiveness test revealed a significant improvement in students’ learning outcomes, with the average pretest score of 65.45 increasing to 88.73 in the posttest and an N-Gain categorized as high. In conclusion, the developed Edugame-based interactive learning media is valid, practical, and effective. The findings imply that this media can serve as an innovative instructional strategy to improve the quality of science learning and support the development of similar media across various subjects and educational levels.